Adaptation to Long-Term Home Non-Invasive Ventilation for People with Chronic Hypercapnic Respiratory Failure: A Qualitative Study - Nur Zahrah Yuko Yacob Hussain; Norasyikin Hassan; Hang Siang Wong; Yingjuan Mok; Piyanee Klainin-Yobas (Nursing Reports)
Background/Objectives: Home non-invasive ventilation use is the primary treatment for improving respiratory function in people with chronic hypercapnic respiratory failure. Non-invasive ventilation has also been studied to understand users’ perspectives. However, no studies have been conducted on how users adapt to non-invasive ventilation in their homes from the early phase of their diagnosis as a long-term utility. Methods: The study employed a descriptive qualitative design guided by Roy’s adaptation model. A purposive sample was used. People with chronic hypercapnic respiratory failure who had used NIV at home for a minimum of six months would be eligible. They were interviewed at a sleep and assisted ventilation centre. Their interviews were audio recorded before proceeding with transcription. Each transcript was thematically analysed. Results: Twenty participants were included in the study, from which six themes emerged. They experienced a common transition, from denying the need for non-invasive ventilation to integrating them into their daily lives at home. Throughout this process, they had emotional turmoil, faced difficulties in keeping their masks on, and improved sleep quality. They also adjusted their social interactions before fully accepting the use of non-invasive ventilation. Their coping strategies in their role functions at home and social interaction were also narrated. Their family members were pivotal in their adaptation period. Conclusions: Gaining insight into individuals’ adaptation experiences can facilitate early identification of potential challenges faced by new users of non-invasive ventilation. This study calls for healthcare professionals to assess users’ understanding of long-term commitment and their living conditions early for a successful NIV adaptation.